2018
DOI: 10.1016/j.ijmst.2017.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Coal rib response during bench mining: A case study

Abstract: In 2016, room-and-pillar mining provided nearly 40% of underground coal production in the United States. Over the past decade, rib falls have resulted in 12 fatalities, representing 28% of the ground fall fatalities in U.S. underground coal mines. Nine of these 12 fatalities (75%) have occurred in room-and-pillar mines. The objective of this research is to study the geomechanics of bench room-and-pillar mining and the associated response of high pillar ribs at overburden depths greater than 300 m. This paper p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 4 publications
(4 reference statements)
0
7
0
Order By: Relevance
“…It is widely used in civil and mining engineering applications (e.g. Tulu et al, 2016;Sears et al, 2018). Its application to geological systems across a range of scales can be found in the literature (e.g.…”
Section: Modelling Methodologymentioning
confidence: 99%
“…It is widely used in civil and mining engineering applications (e.g. Tulu et al, 2016;Sears et al, 2018). Its application to geological systems across a range of scales can be found in the literature (e.g.…”
Section: Modelling Methodologymentioning
confidence: 99%
“…Deep does not mean that the depth, but a mechanical state, which is jointly determined by surrounding rock properties, mining stress and its crustal stress. It refers to the depth of nonlinear physical and mechanical phenomena exhibited by engineering coal and rock masses and the depth range below it 5 – 7 . In terms of failure mechanism of surrounding rock in deep mining roadway, Xue et al 8 revealed that stress evolution and crack development of roadway surrounding-rock are influenced by weathering and horizontal structural stress, and elucidated the asymmetric distortion characteristic of roadway.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, it is not just in China, as one study also showed that over the past decade, rib falls have resulted in 12 fatalities, representing 28% of ground fall fatalities in the United States' underground resulted in 12 fatalities, representing 28% of ground fall fatalities in the United States' underground coal mines. Nine of these twelve fatalities (75%) occurred in room-and-pillar mines [5], causing serious casualties and economic losses [6]. Therefore, an accurate assessment of coal pillar instability and its failure characteristics and an exploration of scientific mining methods that can be employed to prevent coal pillar failure are crucial for the safe mining of adjacent coal seams.…”
Section: Introductionmentioning
confidence: 99%
“…With the help of numerical simulation, a large amount of research has been conducted on the impact of mining-induced stress of adjacent coal seams on the stability of coal pillar clusters, as well as the impact of the instability of coal pillar clusters on the safety of adjacent mining working faces, including the effect of spatial distribution between the upper and lower coal pillars on the stability of double-seam mining [18], the stress distribution of the floor under the residual coal pillar clusters [19], hydraulic fracturing and pressure relief [20], the instability and expansion process of coal pillar clusters [21][22][23], the fatigue damage mechanism and bearing characteristics of multiple coal pillars [17,24], the roof collapse process caused by the instability of the coal pillar cluster [25], movement characteristics of the main roof articulated blocks [26,27], crushed supports [8,28], and the coupling effect of water immersion and mining stress on the stability of resulted in 12 fatalities, representing 28% of ground fall fatalities in the United States' underground coal mines. Nine of these twelve fatalities (75%) occurred in room-and-pillar mines [5], causing serious casualties and economic losses [6]. Therefore, an accurate assessment of coal pillar instability and its failure characteristics and an exploration of scientific mining methods that can be employed to prevent coal pillar failure are crucial for the safe mining of adjacent coal seams.…”
Section: Introductionmentioning
confidence: 99%